Pengaruh Komponen Antimikroba pada Berbagai Ekstrak Bahan Alami Dalam Pengawetan Daging Ayam dan Ikan: Telaah - Nita Khairunnisa; Alifya Khoirun Nisa; M. Athar Fatah; Evina Diningsih; Yasmin Nur Rochmah; Nurul Annazhifah; Ainun Nafisah (Jurnal Sains dan Teknologi Pangan, 2023)
Meat and fish are very easy to spoil because they have a fairly high water content. One of the causes of damage to meat and fish is due to microbes. Microbes can affect the properties of food products, environmental conditions such as pH, water availability, temperature, organoleptic properties, and others. The presence of these microbes can be handled by administering antimicrobial compound content in the process of preserving meat and fish. The content of antimicrobial compounds is found in many plants, such as leaves, flowers, tubers, seeds, rhizomes, fruit, or other parts. This article was created with the aim of comparing the effectiveness of various extracts of natural ingredients that contain antimicrobial compounds on storage time in meat and fish. Based on the results of the research used in this literature review, the use of mango leaf extract in tilapia has the longest shelf life, namely 13 days. While the use of bay leaf extract on chicken meat has a relatively short shelf life of 8 hours. The ability of natural substances as antimicrobials has the potential to be developed as a simple preservative method for chicken and fish meat products.